Mass Dependence of Intermediate Mass Fragments in Multi Fragmentation - Sharma, Bhawna (My University, 2010)
Nuclear multifragmentation, i.e. observation of many fragment reaction channel is one of the most interesting aspect of the heavy ion collisions. The observation of multifragment configuration would correspond to the state of matter intermediate between nuclear liquid (nucleus close to its ground state) and nuclear vapor (assembly of nucleons and lighter mass fragments at high temperature). The study of nuclear multifragmentation is one of the rare possibilities of studying, microscopically, a phase transition in a finite size fluid. We will study the mass dependence of various quantities (like the average density, collision rate, fragment multiplicity etc. by simulating the reactions at the energy 600MeV/nucleon. This study is carried out within the framework of Isospin dependent Quantum Molecular Dynamics model. We have simulated the reactions 197Au79+12C6, 197Au79+26Al13, 197Au+63Cu29 and 197Au79+208Pb82 and collision geometry varied from central to peripheral. Firstly, we will give some details about the experimental, their theoretical scenarios and some of the experimental set ups held in past years in which multifragmentation data obtained. We will also give the theoretical description of the IQMD model. At last we will give qualitative analysis of various results obtained theoretically in multifragmentation and also compare our results with those obtained experimentally from ALADIN experiment.
M.Sc. (Physics)
Keywords: Intermediate mass fragments; heavy ion reactions